A Solution‐Processed High‐Temperature, Flexible, Thin‐Film Actuator. Issue 39 (22nd August 2016) - Wang, Chengwei; Wang, Yanbin; Yao, Yonggang; Luo, Wei; Wan, Jiayu; Dai, Jiaqi; Hitz, Emily; Fu, Kun (Kelvin); Hu, Liangbing
Abstract : A bilayer actuator made of carbon nanotubes (CNTs) and boron nitride (BN) is developed that can withstand high temperatures. The bilayer actuator can be powered quickly to a temperature up to 2000 K within 100 ms and can operate at frequencies from sub‐Hertz to about 30 Hz due to the low heat capacity of the thin CNT layer.